1996
DOI: 10.1097/00007632-199610010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Can Variations in Intervertebral Disc Height Affect the Mechanical Function of the Disc?

Abstract: Variations in disc height may compromise the general conclusions reached from experimental work and analytic studies in which geometric parameters (especially disc height and disc cross-sectional area) are not taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…Most of the data available relate to the lumbar intervertebral discs. Nonetheless, as discussed in prior work (3), biomechanical modeling (26,27,35) and clinical data (24) suggest that increases in disc height may increase risk of injury to that disc. In line with findings from the lumbar spine of the same subjects (1) and also from another bed rest study (3), the results showed persistence of the thoracic disc morphology changes long term after bed rest.…”
Section: Discussionmentioning
confidence: 92%
“…Most of the data available relate to the lumbar intervertebral discs. Nonetheless, as discussed in prior work (3), biomechanical modeling (26,27,35) and clinical data (24) suggest that increases in disc height may increase risk of injury to that disc. In line with findings from the lumbar spine of the same subjects (1) and also from another bed rest study (3), the results showed persistence of the thoracic disc morphology changes long term after bed rest.…”
Section: Discussionmentioning
confidence: 92%
“…The loss of intervertebral disk height may produce a certain instability in the vertebral segment and a relaxation of the oblique fibers of the fibrous annulus, which may contribute to degeneration of the intervertebral disk [14].…”
Section: Discussionmentioning
confidence: 99%
“…Progressive disc degeneration was claimed to be responsible for this phenomenon [9]. The loss of height of the intervertebral disc was shown to produce a significant loss of stability in the segment concerned by relaxing the oblique ring fibres [22,25], an effect that accelerates degeneration again. Kluger et al [18] predicted the amount of kyphosis by measuring the intervertebral disc angles and dividing them by the Cobb angle.…”
Section: Discussionmentioning
confidence: 99%